Factor that influences expatriate employees to attriton problems at Scope International (M) Sdn.Bhd / Mohammad Rizman Niger Mahidin - Niger Mahidin, Mohammad Rizman (Faculty of Business and Management, 2010)
This study is focus on the factor that influences expatriate employees to attrition problems at Scope international (M) Sdn Bhd. The main objective of this project paper is identifying the main factor that contributes to attrition problems at Scope international (M) Sdn Bhd. The research is focusing on expatriate employees at Scope international (M) Sdn Bhd, in four departments. The theoretical framework of this study consists of dependent variable and independent variables. The dependent variable is attrition problems while the independent variables are compensation, working environment, and career advancement. Data collected and evidences are being processed by using Statistical Package for Social Science (SPSS) program. The analysis includes the reliability, frequency distribution, descriptive analysis, and correlation.